Exploring Building Orientation Effects on Mechanical Properties in FDM Technology: A Two-Scale Numerical Analysis - Khalid Essafi; Aissa Ouballouch; Khalid Zarbane (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Additive manufacturing, particularly Fused Deposition Modeling (FDM), has revolutionized the fabrication of customized products, offering an opportunity to make complex parts. However, inherent complexity of these parts demands attention to analyze them, especially in understanding their mechanical properties. This study uses a homogenization method to determine these properties using two scale technique. Our investigation explores the influence of building orientation (Flat, On-edge, Up-right) on longitudinal Young’s modulus. To achieve this, we begin by creating the appropriate Representative Volume Element (RVE) which embodies the microstructure of 3D printed specimens. Subsequently, we calculate orthotropic properties of this RVE using Material Designer tool. Then, these properties are integrated into the subdivided specimen using material Referencess within ANSYS Workbench. And finally, we validate our numerical findings with experimental results.